2017
DOI: 10.1038/s41598-017-04822-2
|View full text |Cite
|
Sign up to set email alerts
|

GWAS follow-up study of esophageal squamous cell carcinoma identifies potential genetic loci associated with family history of upper gastrointestinal cancer

Abstract: Based on our initial genome-wide association study (GWAS) on esophageal squamous cell carcinoma (ESCC) in Han Chinese, we conducted a follow-up study to examine the single nucleotide polymorphisms (SNPs) associated with family history (FH) of upper gastrointestinal cancer (UGI) cancer in cases with ESCC. We evaluated the association between SNPs and FH of UGI cancer among ESCC cases in a stage-1 case-only analysis of the National Cancer Institute (NCI, 541 cases with FH and 1399 without FH) and Henan GWAS (493… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…It is interesting that the inhibition of CYP21A2 by 1 μM abiraterone was observed in a recent study (Malikova et al, 2017). Song et al found 3 SNPs in CYP19A1, which also encodes a cytochrome P450 enzyme, that were associated with a FH of UGI cancer in ESCC cases ( P < 10 −5 ) in a meta-analysis performed by the National Cancer Institute (NCI) and in the Henan GWAS data (Song et al, 2017). As described above, crosstalk between CYP21A2 p.Gln319 * and smoking may promote ESCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that the inhibition of CYP21A2 by 1 μM abiraterone was observed in a recent study (Malikova et al, 2017). Song et al found 3 SNPs in CYP19A1, which also encodes a cytochrome P450 enzyme, that were associated with a FH of UGI cancer in ESCC cases ( P < 10 −5 ) in a meta-analysis performed by the National Cancer Institute (NCI) and in the Henan GWAS data (Song et al, 2017). As described above, crosstalk between CYP21A2 p.Gln319 * and smoking may promote ESCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…After collecting 331 LSCC patients and 349 healthy controls samples and genotyped with PLCE1 rs2274223, we found that the PLCE1 rs2274223-G was significantly associated with a higher LSCC risk, which is similar with its association in ESCC [13][14][15][16][17]. Further stratified analysis demonstrated that age, sex, and smoking status may affect the association.…”
Section: Discussionmentioning
confidence: 54%
“…Different expression profiles of PLCE1, like overexpression or down-regulation, could be found in different types of cancer, and functioned in diverse manners [9][10][11][12]. Large scale genome-wide association (GWAS) studies from different groups had demonstrated that the rs2274223, located in exon 26 of PLCE1, was strongly associated with the risk of ESCC [13][14][15][16][17]. The PLCE1 polymorphisms and its distribution have been…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that family history, smoking, alcohol consumption, aging, and gender are risk factors for ESCC. [10,31,32] Our results demonstrated that family history ( P = .004) and tumor size ( P = .029) were preferentially associated with HLA-DQA1 expression. The percentage of patients expressing HLA-DQA1 is higher for negative family history than that of positive family history.…”
Section: Discussionmentioning
confidence: 65%